The effect of coaching intervention on elite fast bowling technique over a two year period - Ranson, C.; King, M.; Burnett, A.; Worthington, P.; Shine, K. (Sports Biomechanics, 2009)
Fast bowling in cricket is an activity that is well recognised as having high injury prevalence and there has been debate regarding the most effective fast bowling technique. The aim of this study was to determine whether two-year coaching interventions conducted in a group of elite young fast bowlers resulted in fast bowling technique alteration. Selected kinematics of the bowling action of 14 elite young fast bowlers were measured using an 18 camera Vicon Motion Analysis system before and after two-year coaching interventions that addressed specific elements of fast bowling technique. Mann-Whitney tests were used to determine whether any changes in kinematic variables occurred pre- and post-intervention between those who had the coaching interventions and those who didn't. The coaching interventions, when applied, resulted in a more side-on shoulder alignment at back foot contact (BFC) (p = 0.002) and decreased shoulder counter-rotation (p = 0.001) however, there was no difference in the degree of change in back and front knee flexion angles or lower trunk side-flexion. This study has clearly shown that specific aspects of fast bowling technique are changeable over a two-year period in elite level fast bowlers and this may be attributed to coaching intervention.